Anaphoric resolution of zero pronouns in Chinese in translation and reading comprehension - Pellatt, Valerie (The University of Edinburgh, 2002)
The primary aim of the thesis is to investigate some of the processes of reading Chinese text by means of comparing and analysing approximately 100 parallel translations of four texts from Chinese to English. The translations are answers to A Level examination questions. The focus of the investigation is interpretation of the zero pronoun, a common phenomenon in Chinese, which often requires explicitation when translated into English. The secondary aim is to show how translation gives evidence of comprehension, as shown by the variation in interpretation of zero pronouns. The thesis reviews relevant psycholinguistic research into reading, particularly reading of Chinese text. This is followed by reviews of relevant research into translation as a reading activity, and a discussion of its role in language teaching and testing.

The core of the thesis is the discussion of the zero pronoun in Chinese, including discussion of anaphoric choice - the writer's decision on when to use zero in preference to an explicit anaphoric form - and of anaphoric resolution - how a reader decides what a zero pronoun refers to. Anaphoric resolution may be problematic for less experienced readers of Chinese owing to its lack of rich morphological inflection which, in other languages, provides the reader with information. Some of the key ideas on anaphoric choice and resolution are then applied to the analysis of the data in the parallel translations. It would appear that factors in Chinese texts which have an effect on comprehending zero pronouns are antecedent distance, topic persistence, abstraction, multiplicity of arguments and the meaning of the verb. Characteristics of the reader which may affect comprehension of the zero pronoun include personal schemata which may lead to elaborative inferences. On the basis of the data I suggest that mark schemes could be devised on a scalar system encompassing optimal solution, proximal solution and nonsolution, which might help to solve the problem of variability in marking translation.

A by-product of the thesis, and an avenue for further research, is the apparent close relationship between idea units, clause length, punctuation breaks and antecedent distance in Chinese texts and saccade length and working memory capacity in the reader of Chinese.